Study Tabur Beras Kunyit Dance as Welcoming to the Community of Batang Hari Regency - Nurmalinda Zari; Suwardi Endraswara; Agus Cahyono; Dini Kausari (International Conference on Science, Education, and Technology, 2023)
This study aims to describe the Study of the Turmeric Rice Tabur Dance as a Welcoming Culture for the Community in Batang Hari Regency. The problem discussed in this study is how the cultural value of welcoming the community is studied in a turmeric rice sowing dance. This research was conducted using qualitative methods using an ethnochoreological approach. Primary data, based on observations and interviews. Secondary data obtained from references and research. The informants in this study were artists in Batang Hari Regency. The results of this study are that the Tabur Beras Turmeric Dance is a dance offered by the people in Batang Hari Regency in the process of welcoming guests, both guests in formal receptions (graduation, welcoming at work, welcoming at school) and informal welcoming (traditional weddings). Based on this, it gives value and meaning that the turmeric rice sowing dance is a dance that has socio-cultural values in the people of Batang Hari Regency.